2014
DOI: 10.1017/s0263034614000202
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of Richtmyer-Meshkov instability in a cylindrical converging shock tube

Abstract: The interaction of a cylindrical converging shock wave with an initially perturbed gaseous interface is studied experimentally. The cylindrical converging shock is generated in an ordinary shock tube but with a specially designed test section, in which the incident planar shock wave is directly converted into a cylindrical one. Two kinds of typical initial interfaces involving gas bubble and gas cylinder are employed. A high-speed video camera combined with schlieren or planar Mie scattering photography is uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 47 publications
(65 reference statements)
0
12
0
1
Order By: Relevance
“…In this work, the converging RM instability is quantitatively studied in a cylindrically converging shock tube which has already verified its feasibility and reliability for the studies of the converging RM instability in our previous work (Luo et al 2014a;Si et al 2014) and, therefore, only a brief description of this facility is given here. This shock tube consists of a 1.7 m driver section, a 2.0 m driven section and a 1.2 m test section.…”
Section: Experimental Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…In this work, the converging RM instability is quantitatively studied in a cylindrically converging shock tube which has already verified its feasibility and reliability for the studies of the converging RM instability in our previous work (Luo et al 2014a;Si et al 2014) and, therefore, only a brief description of this facility is given here. This shock tube consists of a 1.7 m driver section, a 2.0 m driven section and a 1.2 m test section.…”
Section: Experimental Methodsmentioning
confidence: 82%
“…The converging RM instability has rarely been studied in a shock tube circumstance mainly due to the difficulty of generating a stable converging shock in laboratory conditions. There are only few works on the cylindrically converging shock (Perry & Kantrowitz 1951;Takayama, Kleine & Grönig 1987;Dimotakis & Samtaney 2006;Zhai et al 2010;Luo et al 2015) and, consequently, shock tube experiments on the converging RM instability are scarce (Hosseini & Takayama 2005;Si, Zhai & Luo 2014;Biamino et al 2015;Si et al 2015). Recently, two quantitative shock tube experiments were, respectively, reported in a semi-annular converging shock tube (Ding et al 2017) and a coaxial converging shock tube (Lei et al 2017), in which a reduction of growth rate was found and was ascribed to the RT stabilization effect caused by the interface deceleration motion existing in the converging circumstance.…”
Section: Introductionmentioning
confidence: 99%
“…Based on shock dynamics theory, a convergent shock tube with a special wall profile which can smoothly convert a planar incident shock into a perfect cylindrical one was designed and manufactured (Zhai et al 2010). Subsequently, evolutions of various distorted interfaces accelerated by a cylindrical shock were examined in this facility (Si, Zhai & Luo 2014;Luo et al 2018). The convergent RMI at a single-mode heavy/light interface was realized by a gas lens technique which was originally proposed by Dimotakis & Samtaney (2006) and later extended by Vandenboomgaerde & Aymard (2011), and the experimental results exhibited great potential for studying the convergent RMI (Biamino et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Si等人 [38] 在该激波管中利用肥皂膜技术生成了 SF 6 气泡, 并成功开展了汇聚激波冲击SF 6 气泡的实 验研究, 利用高速纹影方法捕捉到了柱形激波-气泡 图 5 柱形激波冲击SF 6 /air单模界面 [37] Figure 5 Interaction of a cylindrical shock with a single-mode SF 6 /air interface [37] 相互作用的详细过程, 如图6所示. 实验结果表明, 受 Figure 6 Interaction of a cylindrical shock with a SF 6 bubble [38] 图 7 柱形激波与SF 6 气柱相互作用 [39] Figure 7 A cylindrical shock interacting with a SF 6 cylinder [39] 的相互诱导主导着后期界面的演化. Si等人 [39] Zou等人 [44,45] 开展了平面激波冲击椭圆形气柱以及扰 动激波与无扰动界面相互作用的实验研究, 获得了 许多可靠的实验数据.…”
Section: 开展激波加载流体界面的实验研究具有周期短、 初始unclassified